Pinatubo Volcanic Eruption Exacerbated an Abrupt Coral Mortality Event in 1991 Summer. Issue 22 (21st November 2018) - Wu, Chung‐Che; Shen, Chuan‐Chou; Lo, Li; Hsin, Yi‐Chia; Yu, Kefu; Chang, Ching‐Chih; Lam, Doan Dinh; Chou, Yu‐Min; Liu, Yi; Pallister, John; Song, Sheng‐Rong; Chiang, Hong‐Wei; et al.
Abstract: Widespread coral bleaching and mortality associated with global warming have occurred frequently since the phenomenon was first documented in the early 1980s. One such episode that occurred in 1991 over the tropical Pacific‐Indian Ocean region has been attributed to high summer sea surface temperatures. However, we found that sea surface temperature values from the South China Sea region do not provide a comprehensive explanation for the event. Our results, based on time series records of rare earth elements, trace element Al/Ca ratios, and microdomain images from corals in the South China Sea, suggest that this coral mortality event was exacerbated by heavy ash fallout from the cataclysmic 1991 volcanic eruption of Mount Pinatubo. Our findings highlight the profound impact of a volcanic eruption on the modern vulnerable coral reef ecosystems, already under the stress of global warming. Plain Language Summary: Intensive and frequent coral bleaching events have occurred under global warming conditions in recent decades. However, abrupt and extensive mortality episodes, such as which occurred in the South China Sea in mid‐1991, cannot be explained solely on the basis of high summer sea surface temperatures. Here we examine this event in the light of time series of rare earth elements, trace element Al/Ca ratios, and microdomain images for coral samples collected in the South China Sea region. Our results suggest that the second‐largest volcanic eruption of the 20th century, the 1991 Mount Pinatubo volcanic eruption, exacerbated this coral mortality event. The sensitive impacts of such a volcanic eruption on modern vulnerable coral reefs, associated with the stress of thermal conditions, are demonstrated. Key Points: This study reports that the mortality of modern coral reefs could be exacerbated by volcanic eruptions The anomalies of rare earth contents and Al/Ca ratios associated with microdomain images indicate an external impact from the 1991 Pinatubo Our results highlight amplified responses of vulnerable coral reefs to environmental changes under global warming